2022
DOI: 10.1126/science.abm5320
|View full text |Cite
|
Sign up to set email alerts
|

The histone H3.1 variant regulates TONSOKU-mediated DNA repair during replication

Abstract: The tail of replication-dependent histone H3.1 varies from that of replication-independent H3.3 at the amino acid located at position 31 in plants and animals, but no function has been assigned to this residue to demonstrate a unique and conserved role for H3.1 during replication. We found that TONSOKU (TSK/TONSL), which rescues broken replication forks, specifically interacts with H3.1 via recognition of alanine 31 by its tetratricopeptide repeat domain. Our results indicate that genomic instability in the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 63 publications
(47 reference statements)
2
49
0
Order By: Relevance
“…Moreover, it serves as a recruitment platform for multiple histone reader proteins (2). Thus, nucleosomes play an important role in the regulation of chromatin affecting diverse processes such as transcription, replication, and repair (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it serves as a recruitment platform for multiple histone reader proteins (2). Thus, nucleosomes play an important role in the regulation of chromatin affecting diverse processes such as transcription, replication, and repair (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…The identification of TSK/TONSL as DNA repair proteins rescuing broken replication forks, the reported interaction between TONSL and histone H3, and the role of ATXR5/6 in maintaining genome stability in plants via H3.1K27me1 during replication all pointed to a possible link between these proteins. The functional relationship between H3.1, ATXR5/6, and TSK/TONSL was confirmed in a recent study that showed that TSK acts as an H3.1 reader protein via a conserved tetratricopeptide repeat (TPR) domain [ 57 ]. The TPR domain in TSK is composed of 11 repeated TPR motifs (hairpins of antiparallel α-helices) that fold into a channel-like solenoid ( Figure 3 B) [ 57 ].…”
Section: Identification Of Readers and Writers Of H3 Variantsmentioning
confidence: 88%
“…The H3K27 monomethyltransferases ATXR5 and ATXR6 (ATXR5/6), which are represented in all land plants and Tetrahymena thermophila [ 55 , 56 ] but are absent in animals, were the first histone-modifying enzymes shown to specifically methylate the H3.1 variant [ 56 ]. A recent follow-up study related to ATXR5/6 has revealed a universal H3.1 reader domain in the protein TONSOKU (TSK) (known as TONSOKU-LIKE/TONSL in animals), which participates in the regulation of DNA repair during replication [ 57 ]. The discoveries of proteins that can write or read H3.1 are presented in greater depth in the next sections.…”
Section: Identification Of Readers and Writers Of H3 Variantsmentioning
confidence: 99%
See 2 more Smart Citations